ANALISIS PERENCANAAN KEUANGAN SYARIAH PETANI SAWIT DALAM MENINGKATKAN ZISWAF - Amrizal Amrizal; Muhamad Dhani Aswin; Nur Asma; Lia Survika; Lutfi Hidayati (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
Oil palm farmer groups during the harvest season often do not control expenses while during the lean season they experience difficulties and are even trapped in Ijon loans or loan sharks. The purpose of this research is Analyzing the implementation of improving the standard of living of farmers by implementing Islamic financial planning, Analyze Farmers' understanding of contributing to the development of Ziswaf and Analyze how to determine good Islamic financial planning for farmers. The research design used descriptive qualitative with primary data sources in the form of interviews with oil palm smallholders with a sample of 9 farmers from around 150 oil palm smallholders in Kampung Baru Village, Bilah Barat District, Labuhan batu Regency. Qualitative data analysis using Nvivo12 Plus software as a data processing tool. The results of the study prove that firstly, oil palm smallholders have not been able to improve the welfare of the oil palm group based on the sharia financial system. do not understand how to develop Ziswaf assets so that they can be managed optimally. Second, oil palm farmers do not fully understand the contribution of zakat infak and alms assets to the maximum. Third, it is necessary to provide counseling on how to manage Islamic finance and Islamic financial planning based on the Islamic financial system